Measure of The Capital Adequacy in Islamic Banc According to Basle II - محمد سعد عبد (Journal of Economics and Administrative Sciences, 2014)
Capital Adequacy is on of the most importance of financial position element because its role is enhance against varions risks of Banking procese . Which this risks is a result of the nature of its operations , investment , Financing tools in addition , in order to Faced any clients withdraws un expected . So This study aim to measure The Capital Adequacy according to basel II and explin the different risk in the Islamic Bank as aresult to nature and different investment and financing tools as participation speculation , murabah and natures of its assets and liabilities related to commercial banks . Find out we concludes that the Islamic Banks needs to increase the capital more than 8% as stated in the Basel II , and it must be to merge the banks with each other , in order to increase its capital and developed the financing tools , in order to becomes more efficient in the management risks